2023
DOI: 10.1039/d3fo02110f
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for applying probiotics in the antibiotic management of Clostridioides difficile infection

Jingpeng Yang,
Lingtong Meng,
Yanan Li
et al.

Abstract: The choice of the time interval between ‘bacteria and drug’ should be based on the metabolism of antibiotics, different probiotics, probiotic antimicrobial resistance and dosage, the baseline gut ecological environment, and the host immune level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 195 publications
0
2
0
Order By: Relevance
“…The results showed that Bifidobacterium breve could enhance the synergistic effect of these antibiotics through a combination of probiotic and antibiotic metabolites, promoting a greater antibacterial effect against Gram-negative or Gram-positive pathogens. However, the idea remains that probiotics are safer and more effective when they intervene after using antibiotics to combat infection, acting as an adjuvant [131].…”
Section: Probioticsmentioning
confidence: 99%
“…The results showed that Bifidobacterium breve could enhance the synergistic effect of these antibiotics through a combination of probiotic and antibiotic metabolites, promoting a greater antibacterial effect against Gram-negative or Gram-positive pathogens. However, the idea remains that probiotics are safer and more effective when they intervene after using antibiotics to combat infection, acting as an adjuvant [131].…”
Section: Probioticsmentioning
confidence: 99%
“…Numerous studies have focused on investigating the potential impact of L. plantarum in managing diverse gastrointestinal disorders, including infectious diarrhea, antibiotic-associated diarrhea, irritable bowel syndrome (IBS), and inflammatory bowel disease (Ji et al, 2023 ; Kumar et al, 2023 ; Yang et al, 2023 ). L. plantarum 299v ameliorated Escherichia coli -induced intestinal permeability in rats, mitigating a 53% surge in mannitol permeation through the intestinal barrier, as gauged using Ussing chambers (Mangell et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%